Match performance difference between African and Top Five teams in the group stage of the 2022 World Cup - Kessouri, O. (Trends in Sport Sciences, 2023)
Introduction. The analysis of technical performance in soccer helps to identify the most important variables that distinguish successful teams from their unsuccessful counterparts. Aim of Study. This study aimed to determine the difference in the match performance between the African national teams and the Top Five teams in the group stage of the 2022 World Cup. Material and Methods. Data were collected from the Whoscored website for five African national teams (Morocco, Senegal, Ghana, Cameron, and Tunisia) and five successful teams in the tournament (Argentina, France, Croatia, Brazil, and England). Independent t-test was used to compare match statistics between the African teams and the Top Five teams, while the effect size (ES) was used to find determine the magnitude of differences between the groups in those statistics. Results. The results showed that the Top Five teams outperformed the African teams in total shots (p < 0.05; ES = 1.47), shots on target (p < 0.01; ES = 2.68), and shooting from open play (p < 0.05; ES = 1.46), possession (p < 0.001; ES = 3.95), total passes (p < 0.001; ES = 5.90), passing accuracy (p < 0.001; ES = 5.35), short passes (p < 0.001; ES = 6.17), long ball accuracy (p < 0.05; ES = 2.08), and key passes (p < 0.05; ES = 1.53). In contrast, the African teams played more long balls (54.20 ± 6.61 vs 44.00 ± 8.71; ES = -1.31), committed many fouls (p < 0.05; ES = -1.84), made more clearances (p < 0.001; ES = -4.30) and saves by goalkeepers (p < 0.05; ES = -2.02), and received more yellow cards (p < 0.01; ES = -2.21) than their Top Five counterparts. Conclusions. In conclusion, the technical performance of the Top Five teams during the 2022 World Cup was better than the performance of the African teams, especially concerning passing and shooting variables. Therefore, this study can give African coaches an indication of the technical requirements for success in the upcoming World Cup.